EVALUASI PELAKSANAAN PROGRAM POSYANDU LANSIA DI WILAYAH KERJA PUSKESMAS KISMANTORO KABUPATEN WONOGIRI (Studi Kasus di Posyandu Lansia Desa Gambiranom) - Cinta, Cinta Natasya Roviah (Universitas Veteran Bangun Nusantara, 2024)
The coverage of elderly health services at the Kismantoro Public Health Center in 2022 is 16.7%, an increase in 2023, which is 22.9% from the SPM target of 100%. Although it has increased, it is still relatively low. Gambiranom village is low elderly health services, out of 611 elderly only 96 elderly people get health services. The low number of elderly visits to Integrated Health Center is caused by elderly factors, family support, and lack of in-depth socialization. This research is a qualitative descriptive with a case study approach, conducted in September with 4 informants, namely the head of the Public Health Center, midwives coordinator, village midwives, and cadres. Data collection was conducted by in-depth interviews, observation and documentation. Triangulation uses triangulation of sources, namely midwives coordinating The results showed that the input component, including human resources, was sufficient. The cost of Integrated Health Center activities comes from the village which is used for PMT, cadre salaries and the procurement of infrastructure. Infrastructure facilities are not in accordance with regulations. There are SOP but their implementation is sometimes not appropriate. Process components include cadre meetings that are in accordance with regulations, early detection of health checks has not all been carried out. Health counseling is carried out every month, gymnastics is only done once a month, home care services have not been carried out. Recording reporting is still done manually. output component, namely the coverage of elderly health services, has increased but has not reached the expected target. Advice for Kismantoro Public Health Center to provide special training to cadres and provide awards for the most active cadres, as well as record the reporting of Integrated Health Center results online via web/application.